Characteristics and prevalence of plaque psoriasis in patients with palmoplantar pustulosis. (2nd June 2019) - Andersen, Y.M.F.; Augustin, M.; Petersen, J.; Hagenström, K.; Mallbris, L.; Burge, R.; Egeberg, A.
Summary: Background: Palmoplantar pustulosis (PPP) is a chronic pustular skin condition on the palms and soles. The disease is often seen in combination with plaque psoriasis, and whether PPP is a variant of psoriasis has been debated. The disease prevalence of PPP and co‐occurring psoriasis is not yet established and the patient group remains understudied. Objectives: To estimate the prevalence of PPP and co‐occurring psoriasis in three population‐based cohorts and to provide information on patient demographics and characteristics. Methods: Administrative healthcare registries and insurance databases from the U.S.A., Denmark and Germany were used as data sources. Patients with PPP were defined by a single International Classification of Diseases 10th Revision code for PPP during a 1‐year period. Information regarding co‐occurring plaque psoriasis and other comorbidities was extracted. Furthermore, use of antipsoriatic medication was identified. Results: In total 1435, 751 and 1832 patients with PPP were identified in the U.S., Danish and German populations, with estimated 1‐year prevalences of 0·009%, 0·005% and 0·08%, respectively. Plaque psoriasis was present in 14·2–61·3% of patients with PPP. Patients with co‐occurring psoriasis had an overall higher prevalence of psoriatic arthritis. Similarly, medication use was more prevalent in patients with PPP with co‐occurring psoriasis, and especially pronounced was the use of biologic therapies. Conclusions: This large observational study on patients with PPP provides detailed information regarding patient demographics, comorbidities and medication use. The 1‐year prevalence of PPP varied in the three studied populations, possibly due to differences in diagnostics and recording practices. Psoriasis frequently co‐occurred in patients with PPP. What's already known about this topic? Palmoplantar pustulosis (PPP) is a skin disease of the palms of the hands and soles of the feet and is known to be related to psoriasis. Whether PPP is a distinct disease or a variant of psoriasis is not yet established. The condition is understudied in terms of disease prevalence, disease predictors, patient characteristics and comorbidity. What does this study add? In this study using data from three large population‐based cohorts we found low prevalence rates (< 0·1%) of PPP. The prevalence of psoriasis was estimated at between 14·2% and 61·3% in patients with psoriasis. Patients with PPP with co‐occurring psoriasis have a higher prevalence of psoriatic arthritis and use of antipsoriatic drugs. Abstract : Respond to this article Linked Comment: Haidari and Feldman. Br J Dermatol 2019; 181 :887–888 . Plain language summary available online